THEORETICAL BASES OF IMPROVEMENT OF MECHANISMS OF MANAGEMENT OF THE PERSONNEL OF THE ENTERPRISE. - Verbivska, Liudmyla; Kobelia, Zoriana; Verhun, Antonina; Zerkal, Anastasila; Vikhtiuk, Andriy (AD ALTA-JOURNAL OF INTERDISCIPLINARY RESEARCH, 2022)
The article considers the strategic personnel management, which can proceed effectively only within the framework of the strategic personnel management system. It means an ordered and purposeful set of interrelated and interdependent subjects, objects and means of strategic personnel management, interacting in the process of implementing the "strategic personnel management" function. The main working tool of such a system is the personnel management strategy. It is shown that the system of strategic personnel management ensures the creation of structures, information channels, and most importantly, the formation of a personnel management strategy, its implementation and control over this process.
Keywords: Strategic managementmanagementmanagerial skillsorganization's personnel